Hepatocyte Rho-associated kinase signaling is required for mice to survive experimental porphyria-associated liver injury - Jessica M. Herrera; Yun Weng; Tyler J. Lieberthal; Marcus Paoletti; Tammy T. Chang (Hepatology Communications)
Background:. Rho-associated kinases 1 and 2 (ROCK1 and ROCK2) regulate critical cell functions, including actomyosin contractility, apoptosis, and proliferation. Some studies suggest that ROCK inhibition may serve as a treatment for liver fibrosis. More investigation is needed to understand the role of hepatocyte ROCK signaling in vivo, especially in the context of profibrotic liver injury. Methods:. Rock1 fl/fl , Rock2 fl/fl , and Rock1 fl/fl ; Rock2 fl/fl mice were given adeno-associated virus serotype 8 (AAV8)-thyroid hormone-binding globulin (TBG)-Cre to produce targeted gene deletion in hepatocytes, or given AAV8-TBG-Null to generate littermate controls (WT). Mice were then placed on a 0.1% 3,5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) diet to induce liver injury. Results:. Upon DDC-induced liver injury, mice with hepatocyte-specific deletion of ROCK1 alone (R1 KO) or ROCK2 alone (R2 KO) demonstrated minimal differences compared to WT. In contrast, mice with hepatocyte-specific deletion of both ROCK1 and ROCK2 (DKO) showed pervasive early mortality, increased hepatocellular injury, and decreased hepatic function. DDC-injured DKO mice demonstrated markedly distorted liver histology characterized by large cavities in the parenchyma. RNA-seq analysis showed upregulation of cell death, inflammatory, and profibrotic pathways in DDC-injured DKO liver as compared to DDC-injured WT liver. Cdkn1a (gene encoding p21) was one of the most highly upregulated genes in the DKO liver in response to DDC-induced injury. Correspondingly, there was increased hepatocyte nuclear localization of p21 and expression of cleaved caspase-3 in DDC-injured DKO liver, consistent with the activation of p21-mediated caspase-3–dependent apoptotic cell death pathways. ROCK1/ROCK2-deficient primary hepatocytes demonstrated increased susceptibility to both caspase-3–mediated apoptosis and caspase-3–independent forms of cell death in a cell intrinsic manner. Conclusions:. ROCK signaling plays a critical role in mediating hepatocyte cell survival pathways in response to liver injury.